Odnos in stališča medicinskih sester do raziskovanja v klinični praksi zdravstvene nege - Zaluberšek, Jaka (Obzornik zdravstvene nege, 2021)
Introduction: The involvement and use of scientific research in nursing represents an important contribution to the development of the profession. The purpose of this study was to determine nurses' attitudes towards research in clinical practice. Methods: Non-experimental quantitative descriptive and explorative empirical research method was used. The survey was administered to a convenience sample of 104 nurses employed in a clinical setting. Data were collected using an online questionnaire based on a literature review. Descriptive statistics (frequency, minimum, maximum, average and standard deviation) and interference statistics (linear regression, chisquare test, Mann-Whitney U test, Kruskal-Wallis test) were used as part of the statistical methods. Results: The respondents showed mostly positive attitudes towards research in clinical practice (x = 3.44, s = 0.411). Respondents' attitudes towards research are statistically significantly positively influenced by positive work environment for research (R2 = 0.337, p < 0.001) and the fact that the challenges and barriers that nurses face in research do not influence their attitudes towards research (R2 = 0.000, p = <0.932). Discussion and conclusion: The literature shows positive attitudes of respondents towards research, but indicates a number of barriers to research. It is important that nurses are aware of the importance of using research findings in the work process, as this is the only way research will serve its purpose and gain value.
Keywords: clinical practice; employees; klinična praksa; methodology; metodologija; nursing; raziskovanje; research; science; staff; zaposleni; zdravstvena nega; znanost